Comparative Study of Lever Operated Knapsack Sprayer and Controlled Droplet Application Sprayer for Hill Agriculture in the North Eastern India - Dewangan, K N; G.V, Prasanna Kumar (Journal of Agricultural Engineering, 2006)
High rainfall and humidity of the north eastern region of India creates a favourable environment for the prevalence of wide variety of insects, pests, diseases and weeds. For increasing the productivity of the crops there is a need to use an effective sprayer for spraying of pesticides. Therefore, a traditional lever operated knapsack (LOK) sprayer and battery operated hand held controlled droplet application (CDA) sprayer was tested to compare their suitability in the north eastern region. Both the sprayers were operated in the laboratory to study the droplet spectrum. The drift of the CDA sprayer was calculated from the standard data. Feasibility of the sprayers was also tested in the farmer's field. It was found that the CDA sprayer provided higher number of fine droplets which occupy considerable volume of spray and hence cover the target better than LOK sprayer. Further, it was found that the drift of droplets were negligible. In addition, application of concentrated formulation without dilution and even spray of fine droplets results in better deposition of chemicals on target by CDA sprayer as compared to LOK sprayer. Further, CDA sprayer reduced drudgery in spraying.